PENGEMBANGAN MEDIA PEMBELAJARAN JARINUMATIK PADA MATERI SISTEM PERTIDAKSAMAAN NILAI MUTLAK LINIER SATU VARIABEL - Dandy Esa Ardana; Aan Nurfahrudianto; Aprilia Dwi Handayani (UPT Penerbitan Universitas Jember, 2022)
This research was motivated by the results of interviews with mathematics teachers in explaining the subject matter, and the teacher was less varied by using only the lecture method, and the students' lack of understanding of the absolute value material so that the researchers made JARINUMATIK learning media to attract students' attention in learning. This research is (1) to produce learning media JARINUMATIK on the system material inequality system linear absolute value of one variable. (2) To determine student responses to the resulting learning media. This research method uses the R&D (Research and Development) method with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The data collection instrument was in the form of a material expert validation questionnaire, media expert, practitioner expert, and student responses. From the results of the validation of material experts on the JARINUMATIK media, it got an assessment of 91.6%, the validation results from media experts got a value of 89.2%, and the results of practitioner validation got a value of 94.6%, so that the media was categorized as very valid without revision. The results of student responses as a whole got 86.5% and were classified as excellent media. Therefore, the JARINUMATIK learning media on one variable's linear absolute value inequality system is feasible to use. Keywords: Development, JARINUMATIK media, Absolute Value